(untitled) (Nigerian Journal of Technology, 2015)
A laboratory investigation was carried out to determine the shear strength characteristics of compacted cement kiln dust treated lateritic soils for use in liners and covers with up to 12.5% cement kiln dust by dry weight of soil. Specimens were prepared at molding water contents of -2, 0, +2 and +4% of the optimum moisture content at the compactive energy levels of the British standard light (BSL), West African Standard (WAS) or “intermediate” and British standard heavy (BSH). Specimens treated with cement kiln dust met the minimum UCS value of 200 kN/m2 requirement. Generally, the recorded UCS values for lateritic soil – cement kiln dust mixtures produced satisfactory UCS values for all the compactive energy levels considered. However, due to the unavailability of water to meet the hydration demand of the cement kiln dust pozolana no significant improvement in UCS values was recorded beyond 2.5% for cement kiln dust treated specimens compacted at BSH energy level and especially on the dry side of optimum moisture content. http://dx.doi.org/10.4314/njt.v34i2.8